FORMATION OF THE FUNDAMENTALS OF INTERNATIONAL LEGAL REGULATION OF POPULATION MIGRATION PROCESSES DUE TO ENVIRONMENTAL FACTORS: HISTORICAL AND LEGAL ESSAY - Oleksandr Havrylenko (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. The article highlights the process of forming the foundations of international legal regulation of population migration processes due to environmental factors, defining its main stages and identifying the specifics of relevant international legal sources inherent in each period.